The question of questions in Malaysian English - Radina, Mohamad Deli; Asniah, Alias (Issues in Language Studies, 2013)
This paper examined the forms that interrogatives and tag questions can take when used by young Malaysian speakers of English language in oral communication. It offers a description of the features for both question forms as produced by the respondents compared to those of Singapore English (SE) and Standard British English (SBE). The influence of domains and the issue of mother tongue interference in relation to the subjects’ usage of such features will also be investigated. Data were obtained through interviews with 19 Malaysian English (ME) speakers from three major ethnic groups in Peninsular Malaysia and via the recording of six conversations. The results showed various distinctive forms and features of questions in ME used by the speakers. Their usage is found to have a certain link to the domains of conversation. Further analysis revealed that mother tongue interference at the grammatical level, particularly in the case of Malay and Cantonese, plays a major role in determining the structure of ME interrogatives and tag questions as well as the subjects’ unvarying use of the rising intonation as regards the latter. As a result of this interference, ME tag questions used are found to be confined to four forms whilst both the structure of wh- and polar interrogatives experience reduction in the system of tense, auxiliary and operator when used by the subjects.